2016
DOI: 10.1128/jvi.00101-16
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Filoviruses for Identification and Characterization of Monoclonal Antibodies

Abstract: Recent experiments suggest that some glycoprotein (GP)-specific monoclonal antibodies (MAbs) can protect experimental animals against the filovirus Ebola virus (EBOV). There is a need for isolation of MAbs capable of neutralizing multiple filoviruses.Antibody neutralization assays for filoviruses frequently use surrogate systems such as the rhabdovirus vesicular stomatitis Indiana virus (VSV), lentiviruses or gammaretroviruses with their envelope proteins replaced with EBOV GP or pseudotyped with EBOV GP. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…In natural infection, abundant sGP could limit effective neutralization of circulating virus by sGP-cross-reactive antibodies (Ilinykh et al, 2016; Mohan et al, 2012) (Figure 2). However, as mentioned above, we typically saw equivalent or weaker relative neutralization in rVSV relative to the sGP-containing ΔVP30 and EBOV assays.…”
Section: Resultsmentioning
confidence: 99%
“…In natural infection, abundant sGP could limit effective neutralization of circulating virus by sGP-cross-reactive antibodies (Ilinykh et al, 2016; Mohan et al, 2012) (Figure 2). However, as mentioned above, we typically saw equivalent or weaker relative neutralization in rVSV relative to the sGP-containing ΔVP30 and EBOV assays.…”
Section: Resultsmentioning
confidence: 99%
“…The authentic EBOV-eGFP, mouse-adapted EBOV Mayinga (EBOV-MA, GenBank: AF49101) and SUDV strain Gulu were described previously (Bray et al, 1998;Sanchez and Rollin, 2005;Towner et al, 2005). The chimeric infectious EBOV/BDBV-GP and EBOV/ SUDV-GP viruses expressing eGFP were obtained by replacing the gene encoding EBOV GP with that of BDBV (GenBank: KU174137) or SUDV (GenBank: KU174142), respectively (Ilinykh et al, 2016).…”
Section: Virusesmentioning
confidence: 99%
“…Virus neutralization assays were performed in a high-throughput format using the recombinant EBOV-eGFP or chimeric EBOV viruses in which GP was replaced with its counterpart from BDBV or SUDV, as described previously (Ilinykh et al, 2016). Briefly, four-fold dilutions of the respective mAb starting at 200 mg/mL were mixed in triplicate with 400 PFU of the virus in U-bottom 96-well plates and incubated for 1 h at 37 C. Mixtures were applied on Vero-E6 cell monolayer cultures in 96-well plates and incubated for four days at 37 C. In the absence of mAb neutralizing activity, the infection resulted in uniform eGFP fluorescence from the monolayer of cells that was readily detected by fluorescence microscopy.…”
Section: Neutralization Assaysmentioning
confidence: 99%
“…It has been found that neutralization titers obtained with surrogate neutralization assays do not always correspond to those obtained using the native virus [45]. Unfortunately, we were unable to perform PRNT with the infectious ebolaviruses to compare the antibody neutralizing titers measured from our microneutralization assay.…”
Section: Dilution Of Rabbit Serummentioning
confidence: 66%